The opportunity of company’s input through social networks sites: Corporate social responsibility communication’s impacts on stakeholders. Case study of Nestlé and The Body Shop. - Le Beller, Marion (2011)
Purpose – Consumers are increasingly concerned about reports of questionable corporate practices. Explaining complex issues like CSR policies and activities is critically important nowadays for companies and arouse a need for exchanges and discussions between firms and stakeholders. The purpose of this dissertation is to show how SNSs pages provide the necessary interactivity for these exchanges and incite phenomenon like voicing. The impact of companies’ inputs on stakeholders’ perceptions and responses to such discussions is also explored as levels of commitment to CSR matters differ and of CSR knowledge vary among participants; so stakeholders may express different concerns and behaviour on SNSs.